Grazing and drought in tallgrass prairie: the role of belowground bud banks in vegetation dynamics - VanderWeide, Benjamin Lee (Kansas State University, 2013)
Grazing and drought are instrumental in the development and maintenance of perennial grasslands. In this research I tested the belowground bud bank contribution to tallgrass prairie resistance and resilience when perturbed by grazing and drought. First, I tested the bud bank role in vegetation response to and recovery from severe drought (Chapter 2). I compared above- and belowground responses of experimentally droughted plots to ambient controls and irrigated plots during two years of severe drought and two years of recovery. I found that although aboveground net primary productivity declined 30-60% during drought, bud bank density and demography were insensitive to drought. These results suggest that grassland resistance and resilience when perturbed by drought may be mediated by stability of belowground bud banks. Second, I investigated vegetation and soil nutrient legacies following release from long-term grazing (Chapter 3). I documented a relatively rapid shift in aboveground vegetation within four years of grazer exclusion, with productivity, stem density, and diversity becoming relatively more similar to ungrazed than grazed prairie. The density and composition of the belowground bud bank and soil seed bank shifted more slowly, remaining more similar to grazed than ungrazed prairie. Responses of soil nutrients to removal of grazers varied, and in some cases was affected by recent fire history. These results demonstrate the contribution of belowground propagules to the maintenance of a diverse plant community both during grazing and after grazers are removed. Finally, I examined short-term vegetation responses to both drought and grazing (Chapter 4). Despite extreme drought and simulated grazing that reduced productivity and increased mortality of individual stems, the dominant C4 grasses maintained a stable bud bank. Aboveground net primary productivity and bud bank density of sedges and forbs, however, were reduced by both drought and grazing. This differential response of species to extreme drought and grazing led to shifts in community composition and species diversity over one growing season. Across drought and grazing treatments, live rhizome biomass was highly correlated with bud bank density and may be a useful, more easily measured index of bud bank density.
Keywords: Bud bank; Tallgrass prairie; Grazing; Drought; Resistance and resilience; Seed bank; Ecology (0329); Plant Biology (0309)